Solid Lipid Microparticles as a Delivery Carrier for Turmeric Crude Extract Containing Curcuminoids - Tiyaboonchai, Waree; Srisopa, Premnapa; Viyoch, Jarupa; Ingkaninan, Kornkanok (Asian Health, Science and Technology Reports, 2007)
Solid lipid microparticles comprising mixtures of stearic acid, glyceryl monostearate and medium chain triglyceride and containing turmeric crude extract were successfully developed in a one-step procedure, using a hot emulsion technique followed by high speed homogenization. A yellowish cream with a plastic flow behavior and thixotropic characteristics was obtained. Light microscopic investigations revealed that the turmeric extract loaded solid lipid microparticles possessed a narrow size distribution, ranging from 1-7 µm with high entrapment efficacy up to 100%. Dissolution studies using Franz diffusion cells demonstrated a fast release behavior suggesting that the curcuminoids were adsorbed on the particle surface. The stability of curcuminoids in the solid lipid microparticles could be maintained for at least 6 months in the lipidic preparation formulated together with Tween 80.